Real options approach: Case study applied to a nursery to produce Eucalyptus forest seedlings in Brazil - Martins, Jorge C. [UNESP]; Camargo, Diego A. [UNESP]; Munis, Rafaele A. [UNESP]; Simões, Danilo [UNESP] (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria (INIA), 2022)
Aim of study: We checked if an infrastructure investment project for a nursery to produce Eucalyptus forest seedlings using the real options approach was economically viable, in order to verify the influence of the deferral, expansion and abandonment options on the investment project value, as well as their concatenation. Area of study: Our study was based on technical-economic coefficients of a nursery infrastructure to be installed in the São Paulo’s state Midwest region, Brazil. Materials and methods: The investment was assessed by addressing the uncertainties inherent in the investment pro-ject. We used the dynamic model for real option approach and, to determine the volatility of the project, we applied the Monte Carlo simulation method. As real options for the project, we employed deferral, expansion, and abandonment. Main results: Using the traditional valuation methodology, we obtained a negative static net present value of USD 50,957. When incorporating the real options of the abandonment, deferral and expansion in the form of managerial flexibility to forest managers, we obtained the expanded net present value of USD 216,498, that is, 524.8% of valuation. The traditional method of investment evaluation undervalues the project in infrastructures to produce Eucalyptus forest seedlings nursery, and the increase in managerial flexibility, through the real options for deferral, expansion and aban-donment, promotes value to forest managers and enables the feasibility of the project. Research highlights: Infrastructure investment project for a nursery to produce Eucalyptus forest seedlings is not economically viable through the traditional economic evaluation techniques. However, by incorporating managerial flexibilities, through real options, the investment project was valued and it became economically viable.
Keywords: Additional geometric Brownian motion; investment decision-making; irreversibility; Monte Carlo; net present value; uncertainty; underlying asset